2016
DOI: 10.1111/zoj.12310
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny and revision of the Neotropical genusGrumichella Müller (Trichoptera: Leptoceridae), including nine new species and a key

Abstract: The systematics of the Neotropical caddisfly genus Grumichella Müller (Leptoceridae: Grumichellinae) are reviewed. Diagnoses, descriptions and illustrations are provided for four previously described species, G. aequiunguis Flint, 1983, G. flaveola (Ulmer, 1911), G. pulchella (Banks, 1910) and G. rostrata Thienemann, 1905, and nine new species: G. blahniki sp. nov. (Peru), G. boraceia sp. nov. (Brazil), G. cressae sp. nov. (Venezuela), G. jureia sp. nov. (Brazil), G. leccii sp. nov. (Brazil), G. muelleri sp. n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 31 publications
0
6
0
2
Order By: Relevance
“… Holzenthal (1988b) illustrated cases of several unassociated species, and suggested that the genus was likely more species rich than previously known. This supposition was recently corroborated by Calor et al, (2016) who decribed 9 new species from Brazil, Peru, and Venezuela, bringing the genus total to 13 species.…”
Section: Catalogmentioning
confidence: 66%
See 3 more Smart Citations
“… Holzenthal (1988b) illustrated cases of several unassociated species, and suggested that the genus was likely more species rich than previously known. This supposition was recently corroborated by Calor et al, (2016) who decribed 9 new species from Brazil, Peru, and Venezuela, bringing the genus total to 13 species.…”
Section: Catalogmentioning
confidence: 66%
“…leccii Calor and Holzenthal, in Calor et al, 2016:152 [Type locality: Brazil, São Paulo, Jundiai, Serra do Japi, P.S. 11, stream before reservoir, 23°14'30"S, 46°57'16"W; MZUSP; ♂; ♀; larva; larval case; pupa; pupal case].…”
Section: Catalogmentioning
confidence: 99%
See 2 more Smart Citations
“…Antonelli, et al (2009) se refieren a la elevación de la Cordillera de los Andes como un impulsor de la diversificación neotropical en un escenario consistente con la diferenciación alopátrica, en la cual la topografía compleja de los Andes restringe el flujo de genes (Bilton, et al, 2001;Salgado-Roa, et al, 2018). Se ha reportado que Grumichella se encuentra en pequeñas cascadas y superficies rocosas de aguas rápidas en pequeños arroyos de montaña; una de sus características más importantes es el uso de seda para ayudar a mantener la larva en la corriente y unas patas gruesas con garras en los tarsos modificados (Calor, et al, 2016). En la Cordillera Oriental hay varias quebradas con estas características, entre ellas, La Encenilla, uno de los puntos de muestreo en el presente estudio.…”
Section: Resultados Y Discusiónunclassified